Economic benefit of using testosterone gel (used externally) in men with diabetes mellitus and testosterone deficiency - Alexandr A. Astapovskiy; Alina A. Bagdasaryan; Konstantin I. Aref’ev; Svetlana Y. Serebrova; Evgeniya V. Shikh; Vladimir N. Drozdov (Сахарный диабет, 2019)
BACKGROUND: High prevalence of type 2 diabetes mellitus (T2DM) and its input to the increase of mortality indicate that social and economic value of this disease and financial burden are great. Testosterone replacement therapy (TRT) enhances the effectiveness of T2DM treatment. A research was conducted to assess if Androgel® therapy in diabetic men is cost-effective. OBJECTIVES: Defining of economic benefit of adding “Androgel” to the T2DM treatment in men with testosterone deficiency. MATERIALS AND METHODS: Economic modeling and results of other clinical studies were used in the analysis. A guildeline of The Scottish Intercollegiate Guidelines Network (SIGN) was used for clinical study selection, development of economic modelling and study design, assessment of study quality. The study analyzed clinical effects (fasting morning glycemia, glycosylated hemoglobin, HOMA index) and mortality reduce. RESULTS: It was shown that TRT can help to reduce costs of glycemic control, to increase efficiency in terms of cost-effectiveness analysis. Target HbA1c value can be reached by additional cost of 569.39 roubles for every patient. There is a possible additional income from 454.100 to 8.896.186 rubles though reduced mortality. CONCLUSION: Thus, testosterone replacement therapy was shown as cost effective due to reduced costs. The analysis demonstrated HbA1c target achievement and, as a result, reduction of the T2DM outcomes and reduced mortality. There is a possible additional income from 454.100 to 8.896.186 rubles per year.